2018
DOI: 10.1523/jneurosci.2011-17.2018
|View full text |Cite|
|
Sign up to set email alerts
|

Neurogenesis during Abstinence Is Necessary for Context-Driven Methamphetamine-Related Memory

Abstract: Abstinence from methamphetamine addiction enhances proliferation and differentiation of neural progenitors and increases adult neurogenesis in the dentate gyrus (DG). We hypothesized that neurogenesis during abstinence contributes to context-driven drug-seeking behaviors. To test this hypothesis, the pharmacogenetic rat model (GFAP-TK rats) was used to conditionally and specifically ablate neurogenesis in the DG. Male GFAP-TK rats were trained to self-administer methamphetamine or sucrose and were administered… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

7
41
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
3
2
1

Relationship

2
4

Authors

Journals

citations
Cited by 38 publications
(48 citation statements)
references
References 88 publications
7
41
0
Order By: Relevance
“…Prior to the present work, it was unknown if dentate gyrus ABGCs were involved in the retrieval or extinction of recent versus remote reward‐associated memories in the context of opiate use. Of particular relevance to the current work, ABGCs appear to play roles in the temporal separation of events (Aimone et al, ; Rangel et al, ), discrimination of similar contexts (Guo et al, ; Rangel et al, ; Tronel et al, ), memory consolidation (Kitamura & Inokuchi, ), and in the extinction of reward memories (Deschaux et al, ; Castilla‐Ortega, Blanco, et al, ; Galinato et al, ). These roles fit with the known role of the hippocampus and brain regions upstream of the hippocampus, dentate gyrus, and ABGCs in the processing of recent and remote memory (Hales et al, ).…”
Section: Discussionmentioning
confidence: 88%
See 2 more Smart Citations
“…Prior to the present work, it was unknown if dentate gyrus ABGCs were involved in the retrieval or extinction of recent versus remote reward‐associated memories in the context of opiate use. Of particular relevance to the current work, ABGCs appear to play roles in the temporal separation of events (Aimone et al, ; Rangel et al, ), discrimination of similar contexts (Guo et al, ; Rangel et al, ; Tronel et al, ), memory consolidation (Kitamura & Inokuchi, ), and in the extinction of reward memories (Deschaux et al, ; Castilla‐Ortega, Blanco, et al, ; Galinato et al, ). These roles fit with the known role of the hippocampus and brain regions upstream of the hippocampus, dentate gyrus, and ABGCs in the processing of recent and remote memory (Hales et al, ).…”
Section: Discussionmentioning
confidence: 88%
“…self‐administration (Noonan et al, ), (c) methamphetamine i.v. self‐administration (Galinato et al, ), and (d) morphine self‐administration (Bulin et al, ). Interestingly, pharmacological enhancement of adult hippocampal neurogenesis also enhances extinction of a cocaine place memory in mice (Ladrón de Guevara‐Miranda et al, ).…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…For example, we used BrdU to tag cells either 20h or 2 weeks after extended access methamphetamine selfadministration, and our findings indicate that withdrawal and abstinence from methamphetamine increase survival of BrdU cells (Recinto et al, 2012;Galinato et al, 2018a). Investigation of endogenous markers of proliferation, e.g., Ki-67-labeled dividing cells [Ki-67 is expressed in actively dividing neural stem cells and provides an estimate of net proliferation (Gerdes et al, 1984)] during protracted abstinence indicated that abstinence from drug use increased the population of progenitor cells that were neuroblasts or preneuronal progenitor cells (Recinto et al, 2012;Sobieraj et al, 2016;Galinato et al, 2018b). (Brown et al, 2003)].…”
Section: Discussionmentioning
confidence: 65%
“…The hippocampus plays a substantial role in context-driven reinstatement of methamphetamine seeking (Hiranita et al, 2008), and the plasticity in the DG of the hippocampus also regulates context-driven methamphetamine seeking (Galinato et al, 2018a;Galinato et al, 2018b). Previously, in male rats we injected BrdU immediately after an extended access methamphetamine self-administration session to tag dividing neuroblasts and progenitor cells during methamphetamine experience and continued extended access sessions for 4 weeks.…”
Section: Discussionmentioning
confidence: 99%